Highly specific differentiation of MSCs into neurons directed by local electrical stimuli triggered wirelessly by electromagnetic induction nanogenerator. (September 2022) - Liang, Linlin; Liu, Chao; Cai, Pingqiang; Han, Shuwei; Zhang, Ruitong; Ren, Na; Wang, Jingang; Yu, Jing; Shang, Shuo; Zhou, Weijia; Qiu, Jichuan; Mao, Chuanbin; et al.
Abstract: Transdifferentiation of mesenchymal stem cells (MSCs) into neurons provides a practical way for neurodegenerative diseases as alternatives to neural stem cells, but is confronted with challenges to get well-differentiated and mature neurons. In this work, a wirelessly triggered local electrical stimulation system was established to specifically induce neuronal differentiation from rat bone-marrow-derived MSCs (rBMSCs) by coupling a highly conductive and flexible multi-wall carbon nanotube (MWCNT) membrane with a rotating magnetic field. Without nerve-inducing factors, a nearly 100% yield of differentiated neurons was realised without the presence of astrocyte cells by the localized electrical stimuli mediated from electromagnetic induction nanogenerator. Neuronal functions were revealed by rapid spontaneous [Ca 2+ ] i-transient peaks under neurotransmitter action. This novel therapeutic strategy for neurodegenerative disease was further demonstrated in vivo, where the successful neural differentiation of exogenous rBMSCs driven by external magnetic-filed accelerated the brain recovery. This wireless electric stimulation system shows promising effects on neuron differentiation and offers a new perspective in nerve repair without glial scarring. Graphical Abstract: Electromagnetic induction nanogenerator driven MWCNT membrane for growth factor-free neural differentiation of rBMSCs solely into functional neurons, while limiting glia scarring during neuron repair. ga1 Highlights: Electromagnetic induction driven MWCNT membrane provides strong wireless electrical signals. Wireless electrical signals induce solely functional neuron differentiation of adult stem cells. Exogenous rBMSCs can be differentiated into neuron cells in vivo with wireless electrical signals.